2006
DOI: 10.1111/j.1741-1130.2006.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical Conditions and Healthcare Utilization among Adults with Intellectual Disabilities Living in Group Homes in New York City

Abstract: The shift in living situations for adults with intellectual and other developmental disabilities (ID/DD) from family homes to group homes has raised questions about their healthcare needs and access to appropriate healthcare services. This study was undertaken to describe the disability characteristics and medical conditions in a sample of adults living in group homes in order to better understand the relationship of these variables with patterns of healthcare utilization. We examined the demographic and disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Based on evidence-based guidelines, practices can systematically identify high-risk patients. In the case of PHC, the most common primary diagnoses were diabetes, hypertension, and hyperlipidemia, a finding that is consistent with prior research related to individuals with IDDs (Levy et al, 2006;Tyler, Schramm, Karafa, Tang, & Jain, 2010). Having such knowledge allows health care providers to identify at-risk patients who could benefit from more intense, evidence-based interventions.…”
Section: Identifying and Managing Patient Populationssupporting
confidence: 72%
“…Based on evidence-based guidelines, practices can systematically identify high-risk patients. In the case of PHC, the most common primary diagnoses were diabetes, hypertension, and hyperlipidemia, a finding that is consistent with prior research related to individuals with IDDs (Levy et al, 2006;Tyler, Schramm, Karafa, Tang, & Jain, 2010). Having such knowledge allows health care providers to identify at-risk patients who could benefit from more intense, evidence-based interventions.…”
Section: Identifying and Managing Patient Populationssupporting
confidence: 72%
“…90 The pooled prevalence of T2DM was 7.6%. The prevalence of any diabetes was 8.7%; this ranged from 2% 84 to 11% 95,102,117 (data not presented).…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 93%
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Studies have shown that people with intellectual disabilities have a high prevalence of overweight and obesity (Rimmer & Wang, 2005;Yamaki, 2005). Several factors may contribute to this pattern, including living in community versus institutional settings (Krauss & Seltzer, 1986;Janicki & Jacobson, 1986;Levy et al, 2006); engaging in high-risk behaviors, such as adopting poor diets and physical activity patterns (Pitetti, Rimmer, & Fernhall, 1993;Draheim, McCubbin, & Williams, 2002;Draheim, Williams, & McCubbin, 2002a;Draheim, Williams, & McCubbin, 2002b); and being treated with certain psychotropic medications (Spreat, Conroy, & Fullerton, 2004). However, few studies have explored these and other clinical and behavioral characteristics as potential risk factors for obesity and CHD in samples of people with ID with different levels of intellectual impairment and origin of impairment (Merriman, Haw, Kirk, & Stubbs, 2005;Draheim et al, 2002).…”
Section: Abstract Cardiovascular Disease Obesity Primary Carementioning
confidence: 98%